Sifat Allah Melalui Analogi Kesetiaan Ibu - Vinny Elvira Walintukan; Farel Yosua Sualang (Te Deum (Jurnal Teologi dan Pengembangan Pelayanan), 2025)
This research examines one of God's attributes, namely the divine faithfulness, through the analogy of a mother's faithfulness to her child in Isaiah 49:14-15. Previous research by Greene tended to focus solely on the feminine imagery of Yahweh as a conceptual metaphor, whereas this text actually contains a more complex analogy. The method used is thematic analysis within the scope of systematic theology, following biblical exegetical interpretation steps including analysis of the salvation prophecy genre and specific analysis of the analogy. The research findings reveal that God's attribute of faithfulness encompasses three aspects: covenant, intimacy, and transcendence. These aspects complement each other in explaining God's faithfulness within His salvation plan for His people, thus providing a biblical theological foundation for building the spirituality of believers.